Relationship of secretion pattern and MPB70 homology with osteoblast-specific factor 2 to osteitis following Mycobacterium bovis BCG vaccination. - Ulstrup, J C (1995)
Significant homology was found between MPB70 and each of four repeat domains of osteoblast-specific factor 2 (OSF-2). Two internal homology regions within each repeat domain of OSF-2 presumed to be related to the active site(s) of this bone adhesion molecule showed the highest homology. A literature search concerning osteitis after Mycobacterium bovis BCG vaccination in neonates revealed that MPB70-high-producer substrains were associated with an increased incidence of osteitis following vaccination. These observations indicate that the function of MPB70 is related to the interaction between bacilli and the host following vaccination or infection with mycobacteria.